2013
DOI: 10.1177/1039856213496856
|View full text |Cite
|
Sign up to set email alerts
|

The role of trainees as clinical teachers of medical students in psychiatry

Abstract: The role that trainees play as clinical teachers should be acknowledged and supported. Further development of research and scholarship in medical education is needed to determine how best to teach trainees to teach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The teaching of specific areas of psychiatry, such as child and adolescent psychiatry 25 , competent psychopharmacology 26 , community psychiatry 27 or substance abuse 8 may need a more detailed analysis. We are particularly interested in the potential role of trainees as clinical teachers of medical students in psychiatry 28 ; and are also supportive of the need to try to homogenize the core curricula across medical schools 23 . Finally, we are also convinced, as our teachers McHugh and Slavney 29 , that teaching psychiatry may provide notable pleasure and lasting satisfaction 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The teaching of specific areas of psychiatry, such as child and adolescent psychiatry 25 , competent psychopharmacology 26 , community psychiatry 27 or substance abuse 8 may need a more detailed analysis. We are particularly interested in the potential role of trainees as clinical teachers of medical students in psychiatry 28 ; and are also supportive of the need to try to homogenize the core curricula across medical schools 23 . Finally, we are also convinced, as our teachers McHugh and Slavney 29 , that teaching psychiatry may provide notable pleasure and lasting satisfaction 30 .…”
Section: Discussionmentioning
confidence: 99%
“…New technologies have multiple advantages for both students and universities in terms of accessibility and costeffectiveness. E-learning can assist institutions to deal with challenges such as rising enrolments, funding cuts and increasing demands on staff and resources (Lambert,1991;Lambert, Kirkby and Dunn,1997;Hickie, Nash and Kelly, 2013). Simple easily-deliverable resources, such as video lectures, can allow for standardised teaching across geographically diverse sites and assist with course delivery and importantly, allow greater flexibility of access for students.…”
Section: Introductionmentioning
confidence: 99%
“…5 In the study by Hickie et al, almost two-thirds of psychiatric trainees viewed teaching as part of their role, but less than half felt supported in their role by their supervisors. 6 Lampe et al have found that enthusiastic and dedicated clinical teachers were rated positively by medical students at the end of their clinical attachments in psychiatry. 7 Microteaching was initially developed to improve the teaching skills of high-school teachers.…”
mentioning
confidence: 99%